Resiliencia y clima en el aula en estudiantes de la Institución Educativa C.E.B.A Avanzado Eugenio Rivera Lopez, Islandia 2022 - Arche Lliuyacc, Evangelina (2023)
The objective was: To determine the degree of relationship between Resilience and Classroom Climate with students. The problem posed was: What is the degree of relationship between Resilience and Classroom Climate with students? The design was non-experimental transectional correlational with 2 variables: V.I (X): Resilience. V.D (Y): Classroom Climate. The population was 93 students. The sample was made up of 100% of the student population of the educational institution C.E.B.A. Advanced No. 60276 "Eugenio Rivera López" Iceland 2022. The sample will be selected by convenience. The most important results are: X2t = 9.48 X2c = 36.14, gl = 4, p < 0.05, so Resilience is related with a moderate degree with Classroom Climate in students demonstrating the association between the variables the contingency coefficient was used obtaining: r = 0.72.